Retailers must focus on the growing cyberthreat landscape. Issue 2 (February 2017) - Schenk, Gert-Jan
Abstract : High street retailer Next recently announced a fall in sales over the pre-Christmas period, revealing that profits for 2016 will be £792m, which is at the lower end of its original forecasts. It added that this figure could fall by £7m "depending on trade in January", highlighting just how important the New Year shopping sales can be to a retailer's overall profits. Whether it is online or instore, Brits flock to bag themselves the best post-Christmas clearance deals in January. But there's a problem – retailers often overlook the additional security that is needed to supplement this increased interest in spending.